The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1074/jbc.ra119.010063
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of F-box proteins reveals a new branch of the yeast mating pathway

Abstract: The mating pathway in yeast Saccharomyces cerevisiae has long been used to reveal new mechanisms of signal transduction. The pathway comprises a pheromone receptor, a heterotrimeric G protein, and intracellular effectors of morphogenesis and transcription. Polarized cell growth, in the direction of a potential mating partner, is accomplished by the G-protein ␤␥ subunits and the small G-protein Cdc42. Transcription induction, needed for cell-cell fusion, is mediated by G␤␥ and the mitogen-activated protein kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 146 publications
1
12
0
Order By: Relevance
“…Another PTM that may be involved in the regulation of the pheromone signaling pathway is ubiquitination [ 75 ]. Ste18 was detected as a ubiquitinated protein in a large-scale MS analysis [ 41 ], with positions K26 and K41 identified as potential ubiquitination sites.…”
Section: Discussionmentioning
confidence: 99%
“…Another PTM that may be involved in the regulation of the pheromone signaling pathway is ubiquitination [ 75 ]. Ste18 was detected as a ubiquitinated protein in a large-scale MS analysis [ 41 ], with positions K26 and K41 identified as potential ubiquitination sites.…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up analysis, it was shown that while the F-box protein Cdc4 selectively targets Gpa1, other F-box proteins target downstream components of the pheromone-signaling pathway as follows: Dia2 selectively limits pheromone-induced vacuolar targeting; Ucc1 selectively limits MAPK induction; and Pfu1 is needed for proper mating morphogenesis and the disassembly of unproductive mating projections (45).…”
Section: Jbc Reviews: G Protein Ubiquitinationmentioning
confidence: 99%
“…Prominent among these are the mammalian muscarinic cholinergic and βadrenergic receptors, which bind to acetylcholine and epinephrine, respectively (73-78). Likewise, we have shown that the pheromone GPCR in yeast promotes vacuolar delivery of cytoplasmic contents (38,79). Whereas the response to nitrogen and potassium requires Complex I of the yeast PI 3-kinase, mating pheromone requires Complex II.…”
Section: Discussionmentioning
confidence: 91%
“…To enable high-throughput comparison of autophagy responses across diverse nutritional conditions, we used Rosella, a fluorescent reporter of autophagy ( Figure 1A) (37,38). Rosella is comprised of super-ecliptic pHluorin (green, pH sensitive) fused with DsRed.T3 (red, pH stable).…”
Section: Potassium Starvation Promotes Autophagymentioning
confidence: 99%